Data for: Identifying genetically redundant accessions in the globally largest cassava collection - Carvajal-Yepes, Monica; Ospina Colorado, Jessica Alejandra; Aranzales Rondon, Ericson; Velez Tobon, Monica Lorena; Correa Abondano, Miguel Angel; Barbosa Torres, Norma Constanza; Wenzl, Peter (2025)
A diverse panel of cultivated cassava landraces and improved lines were genotyped using DArTSeq Technology to identify genetic redundancy within the genebank collection.